Laparoscopic removal of giant gallstones - Anil kumar; Anurag Kumar; Deepak Kumar; Nilmani Paswan; Bindey Kumar (Elsevier, 2020)
The gold standard treatment of gall stones is laparoscopic cholecystectomy, but in case of giant gall stone (when size is more than 5 cm), its removal by laparoscope is slightly difficult. The occurrence of giant gall stones in young patient is extremely rare. The common reason for this giant gall stone is usually because of its asymptomatic nature. We are presenting three cases of giant gall stones of size 55 × 50 × 45 mm, 58 × 56 × 45 mm and 50 × 56 × 40 mm in 12 years old male, 18 years old female and 14 years old female respectively. To the best of our knowledge only few cases of such giant gall stones are reported. Open cholecystectomy may be required sometimes to remove such giant gallstone. The slight increase in skin incision at epigastric port at the time of specimen removal is a wise decision to remove the giant gall stone laparoscopically.